Q: What is 6a over 4 plus 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6a + 4 = 5a - 2 means that 6a - 5a = -2 - 4 which gives a = -6

It is 6a + 4

6a + 2

In order to solve something, there needs to be an equation. If I have read your equation right you have: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) This looks like it needs to be simplified. There are two fractions being multiplied, so multiply the numerators and denominators together, giving: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) = ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) Now, simplify the polynomials to remove the squared terms and any common factors: a² - 4 = (a - 2)(a + 2) 2 + 6a = 2(1 + 3a) 3 + 9a = 3(1 + 3a) a² + 5a + 6 = (a + 3)(a + 2) Giving: ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) = ((a + 2)(a - 2)3((1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) This can now be simplified by cancelling out equivalent terms, giving: ((a + 2)(a - 2)3(1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) = ((a - 2)3) / (2(a+3)) = 3(a - 2) / 2(a + 3) = (3a - 6) / (2a + 6)

((2 plus (1 over 4)) plus 3) plus (7 over 8) = 6.12500

Related questions

6a + 4 = 5a - 2 means that 6a - 5a = -2 - 4 which gives a = -6

It is 6a + 4

6a + 2

6a + 8 = 2(3a + 4)

-4 + 10 + 6a - 2a + 3 9 + 4a

The solution for the value of 3a would be -3. The equation would be 6a + 3(4) = 2.

6a^b-18ab^2+24ab

6a - 4 = -2(+ 4 on both sides)6a = 2(divide both sides by 6)a = 2/6a = 1/3

It is not possible to answer the question as the value of a is not known, if the value of a was known, for example 2, you could answer as 6a would be 2x6 which is 12 plus 4 giving a total of 16 until the value of a is known the most correct solution, including the brackets, would be (6a+4)

9a = 6a + 4 subtracting 6a from each side, 3a = 4 dividing each side by 3, a = 4/3

In order to solve something, there needs to be an equation. If I have read your equation right you have: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) This looks like it needs to be simplified. There are two fractions being multiplied, so multiply the numerators and denominators together, giving: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) = ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) Now, simplify the polynomials to remove the squared terms and any common factors: a² - 4 = (a - 2)(a + 2) 2 + 6a = 2(1 + 3a) 3 + 9a = 3(1 + 3a) a² + 5a + 6 = (a + 3)(a + 2) Giving: ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) = ((a + 2)(a - 2)3((1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) This can now be simplified by cancelling out equivalent terms, giving: ((a + 2)(a - 2)3(1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) = ((a - 2)3) / (2(a+3)) = 3(a - 2) / 2(a + 3) = (3a - 6) / (2a + 6)

4y - 4 + 3s + 7 - 6a - 4 = 0 4y + 3s + 7 - 6a - 4 = 4 4y + 3s - 6a - 4 = 4 -7 4y + 3s -6a = 4 - 7 + 4 4y + 3s - 6a = -3 + 4 4y + 3s - 6a = 1 y + 3s - 6a = 1/4 y = -3s + 6a + 1/4 3s = -y + 6a + 1/4 s = -1/3y + 6a + 1/4 -6a = -1/3y + a + 1/4 -a = -1/3y x 1/6 + a + 1/4 x 1/6 a = 1/18y - 1 - 1/24 a = 1/18y - 25/24